Effectiveness of transcutaneous electrical neuromuscular stimulation along with exercises manoeuver in Dysphagia: case series - DARSHNI. R. THAKKAR; D. MALARVIZHI (International Journal of Pharma and Bio Sciences, 2016)
Dysphagia typically refers to difficulty in eating as a result of disruption in the swallowing process. It occurs following stroke with incidence relating to lesion size and location. It has been associated with higher rates of respiratory complications and increased risk of aspiration pneumonia, dehydration and nutritional com-promise. The aim of the study is to find out the effectiveness of TENS along with exercise manoeuvres in the treatment of Dysphagia. The study was Case Series Interventional study with 3 patients, both the genders. The inclusion criteria were Acute Dysphagia less than a month, Dysphagia following Stroke, Trauma and Degenerative disease. All 3 patients received TENS with parameters of 80-100Hz for pulse duration of 300 μs and intensity ranging from 2.5 to 25 mA depending on the patient’s tolerance for 30 minutes and immediately followed by Swallowing Therapy exercise such as Head and Neck Positioning, Shakers and Mendelsohn Manoeuvre, 30 minutes duration for 6 days. Functional Oral Intake Scale (FOIS) was used as the outcome measure. Case 1, FIOS pre score was 1 and post score was 2; Case 2, FIOS pre score was 1 and post score was 3; Case 3, FIOS pre score was 4 and post score was 6. The study concluded that there was effectiveness of Transcutaneous Neuromuscular Electrical Stimulation along with Exercise Manoeuvre in improving oral intake ability and improves the quality of life in Dysphagia patients.